FRI0092 Influence of Temperature and Humidity on Disease Activity in Rheumatoid Arthritis. (15th July 2016) - Mandl, P.; Alasti, F.; Kaltenberger, R.; Krennert, T.; Supp, G.; Landesmann, U.; Smolen, J.S.; Aletaha, D.
Abstract : Objectives: To evaluate whether meteorological parameters influence disease activity in patients with rheumatoid arthritis (RA). Methods: We assessed correlations between individual meteorological variables and clinical measures of disease activity: clinical disease activity index (CDAI), self-reported pain (by visual analogue scale), tender- and swollen 28 joint counts (TJC and SJC). Assessments documented in our RA database as well as the average temperature and relative humidity, obtained from the Central Institute for Meteorology and Geodynamics, were matched on a daily basis for a period of 10 years between 2005 and 2015, and analyzed using generalized estimating equations (longitudinal data analysis). Results: A total of 1437 patients with RA (average disease duration at first visit: 4.88±8.63 years; 77% female, mean CDAI 17.8±11.7, mean time in study: 75 month, mean number of visits during study period: 19) were analyzed. Higher temperature and lower humidity were significantly associated with lower CDAI (p=0.0002, and p=0.0332, respectively). Regarding pain, the effects of temperature showed an interaction with humidity: while lower temperatures were associated with higher pain levels at the low and middle tertile of relative humidity, they corresponded to a lower pain level at the high tertile of relative humidity. Temperature showed a significantly negative correlation with TJC (p<0.0001), while relative humidity showed a significantly positive correlation with SJC (p=0.0321). Similar to pain, there was again an interaction of temperature and humidity in the SJC analysis. Conclusions: In this largest association study of meteorological parameters with RA specific outcomes both temperature and relative humidity were shown to have significant effects on disease activity. Individual measures of disease activity and pain correlated either with temperature or humidity, while the composite CDAI measure correlated with both meteorological variables. These aspects may have to be taken into account in longitudinal analyses of disease activity of RA. Disclosure of Interest: None declared